2009
DOI: 10.1038/emboj.2009.360
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of Streptococcus pneumoniae TIGR4 pili

Abstract: Although the pili of Gram-positive bacteria are putative virulence factors, little is known about their structure. Here we describe the molecular architecture of pilus-1 of Streptococcus pneumoniae, which is a major cause of morbidity and mortality worldwide. One major (RrgB) and two minor components (RrgA and RrgC) assemble into the pilus. Results from TEM and scanning transmission EM show that the native pili are approximately 6 nm wide, flexible filaments that can be over 1 lm long. They are formed by a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 45 publications
7
122
1
Order By: Relevance
“…However, because the linear fiber-like pili of Gram-positive bacteria lack quaternary-level organization (16), it remains largely unknown how these megadalton-scale structures address the mechanical challenges for sustained adhesion.…”
mentioning
confidence: 99%
“…However, because the linear fiber-like pili of Gram-positive bacteria lack quaternary-level organization (16), it remains largely unknown how these megadalton-scale structures address the mechanical challenges for sustained adhesion.…”
mentioning
confidence: 99%
“…In S. pneumoniae, the pilus backbone is formed by covalently associated RrgB units; microscopy efforts have indicated that the molecules are associated with a directionality, in which a noselike protrusion defines the polarity of the fiber (25). The crystal structure of RrgB, fitted into a cryo-EM map of the pilus, confirms this polarity (24,59).…”
Section: Discussionmentioning
confidence: 62%
“…The crystal structure of RrgB, fitted into a cryo-EM map of the pilus, confirms this polarity (24,59). Notably, RrgA and RrgC were suggested as being located at the extremities of the fiber, with RrgC at the base and RrgA at the free end (25). The structure of RrgA revealed a four-domain flexible molecule carrying a von Willebrand factor (VWF) domain capable of recognizing extracellular matrix components (26), whereas RrgB displayed a threedomain fold (24,59).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations